Long-term trends and extreme events of marine heatwaves in the Eastern China Marginal Seas during summer - Xu, Jing; Yan, Yunwei; Zhang, Lei; Xing, Wen; Meng, Linxi; Yu, Yi; Chen, Changlin (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are a type of widespread, persistent, and extreme marine warming event that can cause serious harm to the global marine ecology and economy. This study provides a systematic analysis of the long-term trends of MHWs in the Eastern China Marginal Seas (ECMS) during summer spanning from 1982 to 2022, and occurrence mechanisms of extreme MHW events. The findings show that in the context of global warming, the frequency of summer MHWs in the ECMS has increased across most regions, with a higher rate along the coast of China. Areas exhibiting a rapid surge in duration predominantly reside in the southern Yellow Sea (SYS) and southern East China Sea (ECS, south of 28°N). In contrast, the long-term trends of mean and maximum intensities exhibit both increases and decreases: Rising trends primarily occur in the Bohai Sea (BS) and Yellow Sea (YS), whereas descending trends are detected in the northern ECS (north of 28°N). Influenced jointly by duration and mean intensity, cumulative intensity (CumInt) exhibits a notable positive growth off the Yangtze River Estuary, in the SYS and southern ECS. By employing the empirical orthogonal function, the spatio-temporal features of the first two modes of CumInt and their correlation with summer mean sea surface temperature (SST) and SST variance are further examined. The first mode of CumInt displays a positive anomalous pattern throughout the ECMS, with notable upward trend in the corresponding time series, and the rising trend is primarily influenced by summer mean SST warming. Moreover, both of the first two modes show notable interannual variability. Extreme MHW events in the SYS in 2016 and 2018 are examined using the mixed layer temperature equation. The results suggest that these extreme MHW events originate primarily from anomalous atmospheric forcing and oceanic vertical mixing. These processes involve an anomalous high-pressure system over the SYS splitting from the western Pacific subtropical high, augmented atmospheric stability, diminished wind speeds, intensified solar radiation, and reduced oceanic mixing, thereby leading to the accumulation of more heat near the sea surface and forming extreme MHW events.